Childhood maltreatment and the risk of pre‐pregnancy obesity and excessive gestational weight gain. Issue 3 (19th August 2014) - Diesel, Jill C.; Bodnar, Lisa M.; Day, Nancy L.; Larkby, Cynthia A.
Abstract: The objective of this study was to estimate whether maternal history of childhood maltreatment was associated with pre‐pregnancy obesity or excessive gestational weight gain. Pregnant women ( n  = 472) reported pre‐pregnancy weight and height and gestational weight gain and were followed up to 16 years post‐partum when they reported maltreatment on the Childhood Trauma Questionnaire (CTQ). CTQ score ranged from no maltreatment (25) to severe maltreatment (125). Prenatal mental health modified the association between CTQ score and maternal weight ( P  < 0.15), and thus stratified models are presented. After adjusting for race, prenatal tobacco, marijuana and alcohol use, a one standard deviation (1 SD) increase in CTQ score was associated with a 45% increase in the risk of pre‐pregnancy obesity among the 141 women with elevated anxiety (≥75th percentile on the State Trait Anxiety Inventory) [relative risk, RR (95% confidence interval, CI): 1.45 (1.12, 1.88)], but was not associated among less anxious (<75th percentile) women [RR (95% CI): 1.10 (0.81, 1.51)]. Risk of excessive gestational weight gain was higher [adjusted RR (95% CI): 1.21 (1.07, 1.37)] with every 1 SD increase in CTQ score for anxious women. No association was observed for less anxious women [adjusted RR (95% CI): 0.89 (0.78, 1.02)]. Prenatal depression similarly modified the association between maltreatment and weight gain. Factors such as psychological status and traumatic experiences in early childhood may contribute to pre‐pregnancy obesity and excessive gestational weight gain.